2015
DOI: 10.18632/oncotarget.6523
|View full text |Cite
|
Sign up to set email alerts
|

The CNGRC-GG-D(KLAKLAK)2 peptide induces a caspase-independent, Ca2+-dependent death in human leukemic myeloid cells by targeting surface aminopeptidase N/CD13

Abstract: The CD13 antigen's binding site for the Asn-Gly-Arg (NGR) motif enables NGR-containing chemotherapeutic drugs to be delivered to CD13-positive tumours. Human CD13-positive acute myeloid leukemia (AML) cells proliferate abnormally and escape death. Here, we show that the CNGRC-GG-D(KLAKLAK)2 peptide induces death in AML cell lines (U937, THP-1, NB4, HL-60) and primary blood cells from AML patients. Cell death was characterized as a caspase-independent mechanism, without DNA fragmentation, but phosphatidylserine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 93 publications
0
19
0
Order By: Relevance
“…It was shown that they can induce necrosis after plasma membrane disruption, depending on their L-or D-chirality, 52,53 apoptosis by the upregulation of caspases, 54 the influx of extracellular Ca 2 + , Ca 2 + -mediated DJm disruption and mitochondrial O 2 $ À generation. 55 However, the cationic peptide (KLAKLAK) 2 has been reported to have a potency that is too low for it to be used as an effective anticancer drug. 41 Because BH3-only proteins either directly or indirectly inhibit prosurvival BCL-2 family members, such as BCL-2, BCL-xL, and MCL-1, to increase cellular sensitivity to anticancer agents, efforts were made to develop so-called BH3 mimetics.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that they can induce necrosis after plasma membrane disruption, depending on their L-or D-chirality, 52,53 apoptosis by the upregulation of caspases, 54 the influx of extracellular Ca 2 + , Ca 2 + -mediated DJm disruption and mitochondrial O 2 $ À generation. 55 However, the cationic peptide (KLAKLAK) 2 has been reported to have a potency that is too low for it to be used as an effective anticancer drug. 41 Because BH3-only proteins either directly or indirectly inhibit prosurvival BCL-2 family members, such as BCL-2, BCL-xL, and MCL-1, to increase cellular sensitivity to anticancer agents, efforts were made to develop so-called BH3 mimetics.…”
Section: Discussionmentioning
confidence: 99%
“…The pathway of tumor cell death after administration of the opio‐klak peptide is similar to that reported by Bouchet et al . . Namely, in a short time (5–15 min), an increase in the count of positive cells stained with annexin solution (apoptosis) was noticed.…”
Section: Resultsmentioning
confidence: 98%
“…Thus, it seems that the mechanism of the action of the opio‐klak peptide is similar to that suggested by Bouchet et al . . In the first minutes after administration of the peptide to the cells, an increase in the percentage of cells with phosphatidylserine relocated from inside to outside of the cell membrane is observed (Annexin V‐positive staining) followed by increasing of cells with non‐continuous outer membrane (PI Annexin V positive stainings).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the use of this peptide for anticancer therapy with enhanced apoptotic activity must involve the specific tumor targeting and efficient cellular internalization. Conjugating D (KLAKLAK) 2 with tumor homing moieties, such as NGR motif, RGD peptide, LyP‐1, protein transduction domain (PTD), or antibody, has produced chemical conjugates that are able to accumulate at tumor sites. To further enhance the extracellular and intracellular targeting ability, Zhang and co‐workers designed and prepared a dual‐targeting proapoptotic peptide (DTP) by the conjugation of folic acid (FA) moiety (targeting agent I) and triphenylphosphonium (TPP) cation (targeting agent II) with D (KLAKLAK) 2 to achieve simultaneous tumor cell‐ and mitochondria‐targeted cancer therapy ( Figure a) .…”
Section: Therapeutic Strategies Toward Specific Subcellular Compartmentsmentioning
confidence: 99%